2017
DOI: 10.1148/radiol.2016162535
|View full text |Cite
|
Sign up to set email alerts
|

Is There Long-term Signal Intensity Increase in the Central Nervous System on T1-weighted Images after MR Imaging with the Hepatospecific Contrast Agent Gadoxetic Acid? A Cross-sectional Study in 91 Patients

Abstract: Purpose To evaluate whether there is T1-weighted signal intensity (SI) increase in the dentate nucleus (DN) and globus pallidus (GP) in relation to the middle cerebellar peduncle (MCP), pons, and thalamus after repeated administration of the liver-specific contrast agent gadoxetic acid. Materials and Methods This was an institutional review board-approved, prospectively conducted (written informed consent acquired), cross-sectional study performed in a consecutively selected patient group (n = 91; patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…Gadovist (Gadavist) Gd-DO3A-butrol Macrocyclic Radbruch et al, 8 Cao et al 9 Gadobenate dimeglumine MultiHance Gd-BOPTA Linear, ionic Weberling et al, 10 Ramalho et al 11 Gadoxetic acid disodium Primovist (Eovist) Gd-EOB-DTPA Linear, ionic Kahn et al 13 Ichikawa et al 12 …”
Section: Gadobutrolmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadovist (Gadavist) Gd-DO3A-butrol Macrocyclic Radbruch et al, 8 Cao et al 9 Gadobenate dimeglumine MultiHance Gd-BOPTA Linear, ionic Weberling et al, 10 Ramalho et al 11 Gadoxetic acid disodium Primovist (Eovist) Gd-EOB-DTPA Linear, ionic Kahn et al 13 Ichikawa et al 12 …”
Section: Gadobutrolmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Stability both in in vitro and in vivo, relative to the release of gadolinium (which depends upon both thermodynamic and kinetic stability), has been shown to be markedly superior for the macrocyclic agents when compared with the linear agents. [14][15][16][17] The linear nonionic agents (specifically gadodiamide and gadoversetamide) are also markedly less stable by this measure than the linear ionic ones.…”
mentioning
confidence: 99%
“…Recently, trace amounts of gadolinium have been detected in the brain of patients after several injections of the linear gadolinium-containing contrast agents gadodiamide, gadopentetate dimeglumine, gadobenate dimeglumine, and gadoversetamide. For gadoxetate, one report has indicated a correlation between the number of prior gadoxetate administrations and increase signal on nonenhanced T1-weighted images in the dentate nucleus [107], while a second report did not find such a correlation [108]. Currently it is not known whether persistence of gadolinium in the brain following therapeutic administration of contrast agents is associated with adverse health consequences.…”
Section: Liver Imaging With Gadoxetatementioning
confidence: 99%
“…Historically, some cases of nephrogenic system fibrosis in kidney patients have been reported after the use of gadolinium, and it is contraindicated for renal studies in several institutions. Moreover, new evidence suggests that gadolinium is deposited in the brain …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, new evidence suggests that gadolinium is deposited in the brain. 9 ASL is a noninvasive alternative to study renal physiology where the blood entering the kidneys is used as a contrast agent. Recently, it has been reported that the perfusion in the cortex measured with ASL is affected by kidney diseases.…”
Section: Introductionmentioning
confidence: 99%